Disturbed Violent Offenders in New York, 1985 - Toch, Hans ([Verlag nicht ermittelbar], 1990)
This data collection was designed to investigate the relationship between mental illness and violent involvement over an offender's criminal career and to develop a typology of violent offenders that takes into account both mental health history and substance use history. The collection is organized so that data for the violent offender cohort can be matched with records of offender mental health history, substance abuse history, and criminal career history. The offenders were convicted of statutorily-defined "violent offenses." Included in the collection are variables concerning conviction offenses, intoxication status, victim-offender relationship, injury result, type of violence, employment, marital status, gender, and race. The criminal history file contains variables on dates of arrest or juvenile contacts. The mental history file includes dates of entry and types of mental health services received.